Experimental investigation of directional hydrodynamic coefficients and the effects on wave force due to spreading angles - Ng, C.Y. (Ain Shams University, 2020)
Assessment of wave forces in the design of marine structures considering real ocean properties were reported better represented by short-crested wave statistics. Henceforth, this paper aims to investigate the effect of directional spreading angles for short-crested wave on the prediction of wave forces and hydrodynamic coefficients. The wave surface elevation and forces exerted on bottom fixed vertical cylindrical models in the wave tank by waves with directional spreading angles ranging from 0 to 45 deg were measured experimentally. Based on the measured data, directional hydrodynamic coefficients as function of Keulegan-Carpenter (KC) numbers were derived numerically by the least square method and its effects were analyzed. Force reduction was found due to the directional spreading angles, whereby 1.20 percent of total wave force were reduced with every one deg of angle incremental. Overall, greater reductions are expected for bigger angles as the wave energy distribution area is expected to be increased. Â© 2020 Faculty of Engineering, Ain Shams University